Understanding The Rise of Childfree Marriage: Avoiding Toxic Family, Being Happy and Well Without Children Despite Contradiction With Maqashid al-Sharia - Harahap, Ikhwanuddin; Siregar, Fatahuddin Aziz; Hariyanto, Erie (AL-ISTINBATH : Jurnal Hukum Islam, 2025)
This research aims to understand the phenomenon of increasing childfree marriage as a contemporary social construction and analyze it from the perspective of maqashid al-sharia, especially related to the principle of progeny preservation in Islam. This study uses a descriptive qualitative approach with a field research method. Primary data was obtained through in-depth interviews with two married couples (four informants), each of whom committed to a child-free marriage. The data were analyzed thematically with an eminic and ethical approach, as well as interpretive-descriptive. Research has found that couples' decisions to marry without having children are based on a desire to achieve happiness and well-being throughout their life with their partner, as well as avoiding the creation of a toxic family. These internal factors are reinforced by external factors such as education, economy, and career. Research has also found that wives play a key role in these decisions regarding reproductive rights. From the perspective of Islamic law, although there is no explicit text prohibiting childfree marriage, maqashid al-sharia still emphasizes the importance of the sustainability of offspring. The childfree decision is a conscious choice of a married couple to pursue happiness and well-being without the presence of children, on the grounds of avoiding the potential for toxic families. In the Islamic view, childfree marriage falls within the territory of ijtihadiyyah which requires a legal approach based on maqashid al-sharia and 'illat analysis. Although this phenomenon is socially acceptable, normatively Islam still prioritizes the importance of offspring as part of the purpose of sharia.